Role of Thalamic Projection in NMDA Receptor-Induced Disruption of Cortical Slow Oscillation and Short-Term Plasticity - Kiss, Tamás; Hoffmann, William E.; Scott, Liam; Kawabe, Thomas T.; Milici, Anthony J.; Nilsen, Erik A.; Hajós, Mihály (Frontiers in Psychiatry, 2011)
NMDA receptor (NMDAR) antagonists, such as phencyclidine, ketamine or dizocilpine (MK-801) are commonly used in psychiatric drug discovery in order to model several symptoms of schizophrenia, including psychosis and impairments in working memory. In spite of the widespread use of NMDAR antagonists in preclinical and clinical studies, our understanding of the mode of action of these drugs on brain circuits and neuronal networks is still limited. In the present study spontaneous local field potential (LFP), multi- (MUA) and single unit activity, and evoked potential, including paired-pulse facilitation (PPF) in response to electrical stimulation of the ipsilateral subiculum were carried out in the medial prefrontal cortex (mPFC) in urethane anesthetized rats. Systemic administration of MK-801 (0.05~mg/kg, i.v.) decreased overall MUA, with a diverse effect on single unit activity, including increased, decreased or unchanged firing, and in line with our previous findings shifted delta frequency power of the LFP and disrupted PPF (Kiss et al., Int J Neuropsychopharmacol. 2010). In order to provide further insight to the mechanisms of action of NMDAR antagonists, MK-801 was administered intracranially into the mPFC and mediodorsal nucleus of the thalamus (MD). Microinjections of MK-801, but not physiological saline, localized into the MD evoked changes in both LFP parameters and PPF similar to the effects of systemically administered MK-801. Local microinjection of MK-801 into the mPFC was without effect on these parameters. Our findings indicate that the primary site of the action of systemic administration of NMDA receptor antagonists is unlikely to be the cortex. We presume that multiple neuronal networks, involving thalamic nuclei contribute to disrupted behavior and cognition following NMDA receptor blockade.